Ultrathin polymer-sulfide-based composite electrolyte membrane, preparation method and application

By adding polymer to the sulfide electrolyte and forming an ultra-thin polymer-sulfide-based composite electrolyte membrane, the problem of large thickness of the sulfide electrolyte is solved, and the battery performance is poor is achieved, high ionic conductivity and good mechanical properties are improved. The overall performance of the battery.

CN119481241APending Publication Date: 2025-02-18INST OF ENERGY HEFEI COMPREHENSIVE NAT SCI CENT (ANHUI ENERGY LAB)
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411763372.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-02-18

Smart Images

  • Figure CN119481241A_ABST
    Figure CN119481241A_ABST
Patent Text Reader

Abstract

The invention discloses an ultrathin polymer-sulfide-based composite electrolyte membrane, a preparation method and application, and belongs to the technical field of solid electrolyte. The method comprises the following steps: mixing an acrylate monomer with a UV initiator, adding a sulfide electrolyte solution mixed in advance, stirring at a high speed to obtain a solution containing micro-nano bubbles, and performing UV curing imprinting while heating to form a sulfide electrolyte membrane supported by an acrylic resin adhesive membrane support with a three-dimensional structure; and preparing a mixture solution of PEO and lithium salt / metal chloride, and immersing the mixture solution into the acrylic resin adhesive film / sulfide thin film in a coating manner and the like to obtain the polymer / sulfide-based composite electrolyte film. According to the preparation method, the ultrathin and thickness-controllable sulfide-based composite solid electrolyte membrane can be obtained, and the sulfide-based composite solid electrolyte membrane has higher ionic conductivity, lower interface impedance, better circularity and higher capacity retention ratio.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of solid electrolytes, and in particular relates to an ultra-thin polymer-sulfide based composite electrolyte membrane, a preparation method and an application thereof. Background Art

[0002] Lithium-ion batteries are widely used in the field of new energy vehicles due to their high voltage and high energy density. However, liquid lithium-ion batteries use organic electrolytes and graphite negative electrodes, which leads to safety issues such as explosions. At the same time, the energy density still cannot meet the requirements of long-term battery life. Solid-state batteries can fundamentally prevent thermal runaway by using solid electrolytes instead of flammable organic liquid electrolytes. At the same time, they can achieve a significant increase in energy density when combined with ternary materials. They are the development direction of the next generation of lithium batteries.

[0003] The current mainstream solid electrolytes include oxide electrolytes, polymer electrolytes, sulfide electrolytes and halide electrolytes. Among them, oxide electrolytes have the advantages of good stability and high ionic conductivity, but the rigidity leads to poor interface contact; polymer electrolyte processing technology is relatively mature, and the stability to lithium metal is good, but the low room temperature ionic conductivity and poor thermal stability limit the scope of application. Halide electrolytes have high ionic conductivity, but cannot match the metal lithium negative electrode, and the cost of some raw materials is too high. They are still in the scientific research stage. Sulfide electrolytes are considered to be one of the most promising routes to achieve all-solid-state lithium battery electrolytes because of their very high room temperature ionic conductivity, good softness / plasticity, and low grain boundary impedance.

[0004] However, the brittleness of sulfide electrolytes is relatively high, and the shear modulus reaches 18 to 25 GPa, which means that the prepared sulfide electrolyte must be thicker (>1 mm) to prevent the electrolyte from rupturing and avoid battery failure. But this also leads to a low energy density of the battery, which is very unfavorable for the commercial use of sulfide electrolytes. Therefore, a thinning strategy to reduce the thickness of the sulfide is very necessary. By adding organic matter to the sulfide electrolyte, the thickness of the sulfide can be controlled. At the same time, after the polymer fills the sulfide, it can be filled into the pores of the sulfide to further improve compaction. At the same time, the polymer can prevent the reaction between the sulfide electrolyte and metallic lithium, and improve the stability to lithium metal. Summary of the invention

[0005] One of the purposes of the present invention is to provide a method for preparing an ultra-thin polymer-sulfide based composite electrolyte membrane to solve the problem that the thickness of the sulfide electrolyte is large, resulting in poor battery performance;

[0006] The second object of the present invention is to provide an ultra-thin polymer-sulfide based composite electrolyte membrane;

[0007] The third object of the present invention is to provide an ultra-thin polymer-sulfide based composite electrolyte membrane for use in an all-solid-state battery.

[0008] The purpose of the present invention can be achieved through the following technical solutions:

[0009] In a first aspect, a method for preparing an ultrathin polymer-sulfide based composite electrolyte membrane comprises the following steps:

[0010] S1. Mixing an acrylic ester monomer with a UV initiator, adding a mixed solution of a sulfide electrolyte and a solvent, stirring to obtain a solution containing micro-nano bubbles, and UV curing and imprinting to form a sulfide electrolyte membrane with an acrylic resin film as a support having a three-dimensional structure;

[0011] S2. PEO (polyethylene oxide) and lithium salt are added to acetonitrile, mixed evenly, and then chloride is added and stirred to obtain a polymer mixed solution;

[0012] S3. Apply the polymer mixed solution on the sulfide electrolyte membrane to make it evenly immersed, so as to obtain a polymer-sulfide based composite electrolyte membrane.

[0013] Furthermore, in S1, the weight ratio of the acrylic ester monomer, the sulfide electrolyte and the solvent is (2-10): (90-98): (270-294).

[0014] Furthermore, in S1, the acrylate monomer is one or more of acrylic acid, 2-hydroxyethyl acrylate, hydroxypropyl acrylate, methacrylic acid, 2-hydroxyethyl methacrylate, 2-hydroxypropyl methacrylate, methyl α-cyanoacrylate, and pentaerythritol triacrylate.

[0015] Further, in S1, the UV initiator is one or more of initiator 1173 (2-hydroxy-2-methyl-1-phenylpropanone), initiator 184 (1-hydroxycyclohexylphenyl ketone), initiator 907 (2-methyl-2-(4-morpholinyl)-1-[4-(methylthio)phenyl]-1-propanone), and TPO (2,4,6-trimethylbenzoyl-diphenylphosphine oxide);

[0016] And / or, the amount of UV initiator added is 1-5% by weight of the acrylate monomer.

[0017] Furthermore, in S1, the solvent is a mixture of one or more of toluene, xylene, chlorobenzene, dimethyl carbonate, n-hexane, acetonitrile, tetrahydrofuran, and n-heptane.

[0018] Furthermore, in S1, the sulfide electrolyte includes Li3PS4, Li7P3S 11 , Li 11 Si2PS12 , Li 3.25 Ge 0.25 P 0.75 S4, Li6PS5Cl, Li6PS5Br, Li4GeS4, Li 10 GeP2S 12 , Li 10 SnP2S 12 One or more of .

[0019] Furthermore, in S1, the UV curing imprinting temperature is 30-80° C., and the imprinting speed is 50-150 mm / min.

[0020] Furthermore, in S1, the stirring speed is 2000-5000 rpm, and the stirring time is 10-30 min.

[0021] Furthermore, in S2, the weight ratio of PEO, lithium salt and acetonitrile is (20-50):(1-5):(50-300); and the amount of chloride added is 0.1-0.8‰ of the weight of PEO.

[0022] Further, in S2, the lithium salt is one or more of lithium perchlorate, lithium imide bistrifluoromethanesulfonate and lithium hexafluorophosphate;

[0023] And / or, the chloride is one or more of magnesium chloride, aluminum chloride, zinc chloride and ferric chloride.

[0024] In a second aspect, an ultra-thin polymer-sulfide based composite electrolyte membrane is prepared by the above preparation method.

[0025] In a third aspect, an ultrathin polymer-sulfide based composite electrolyte membrane is used in an all-solid-state battery. The all-solid-state battery comprises a positive electrode, a negative electrode and the ultrathin polymer-sulfide based composite electrolyte membrane prepared by the above preparation method.

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] 1. The present invention provides a method for preparing a polymer-sulfide-based composite electrolyte membrane. The prepared polymer-sulfide-based composite electrolyte membrane has a thickness of 10 to 100 μm and a room temperature ionic conductivity of 0.5 to 10 mS·cm -1 In the process of preparing acrylic resin film, a solution containing micro-nano bubbles is formed by high-speed stirring. At the same time, the acrylate is UV-cured as a support to form an ultra-thin acrylic resin / sulfide composite film with sulfide, which can significantly improve the mechanical strength of the sulfide electrolyte and improve the ability to inhibit lithium dendrites. The film contains a large number of three-dimensional through holes, including holes formed when the bubbles are cured and holes formed by embossing.

[0028] 2. In the present invention, the PEO polymer penetrates into the three-dimensional pores in the form of a solution. After the metal chloride is added, on the one hand, the chloride is complexed with the carboxyl / hydroxyl functional groups of the acrylate, which is beneficial to improve the strength of the structure. On the other hand, the metal ions are complexed with PEO, which is beneficial to reduce the electron cloud density of the PEO chain, enhance the antioxidant ability of PEO to the positive electrode material, and at the same time is beneficial to the dissociation of the lithium salt, thereby improving the ionic conductivity.

[0029] 3. The preparation method of the present invention can obtain an ultra-thin sulfide-based composite solid electrolyte membrane with controllable thickness, which has high ionic conductivity, reduces interface impedance, has good cyclability and high capacity retention rate. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] The present invention will be further described below in conjunction with the accompanying drawings.

[0031] Figure 1 It is a schematic diagram of the preparation process of an ultra-thin polymer-sulfide-based composite electrolyte membrane of the present invention;

[0032] Figure 2 is the XRD spectrum of the composite electrolyte membrane prepared in Example 1 of the present invention;

[0033] Figure 3 is an AC impedance spectrum of the composite electrolyte membrane prepared in Example 1 of the present invention;

[0034] Figure 4 is a linear sweep voltammogram of the composite electrolyte membrane prepared in Example 1 of the present invention;

[0035] Figure 5 is the cycle performance curve of the all-solid-state battery prepared in Application Example 1 of the present invention;

[0036] Figure 6 This is the rate performance curve of the all-solid-state battery prepared in Application Example 1 of the present invention. DETAILED DESCRIPTION

[0037] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0038] Unless otherwise specified, the stirring speed in the embodiments is set according to conventional methods as long as it meets the industry standards.

[0039] Example 1

[0040] See also Figure 1 , a method for preparing an ultrathin polymer-sulfide based composite electrolyte membrane, comprising the following steps:

[0041] S1. 90 parts by weight of Li2P3S 11 Dissolved in 270 parts by weight of toluene to obtain a mixed solution; 2 parts by weight of acrylic acid and 1% by weight of initiator 1173 of acrylic acid were mixed, and then the pre-mixed mixed solution was added, and stirred at a speed of 4000 rpm for 20 minutes to obtain a solution containing micro-nano bubbles, and UV-cured imprinting was performed using a nano-imprinter, and the imprinting temperature was set to 80°C, the imprinting speed was set to 150 mm / min, and the imprinting template parameters were as follows: the template shape was cylindrical, the protrusion height was 5 μm, and the spacing was 10 μm. UV-cured imprinting was performed while heating to form a sulfide electrolyte membrane with a three-dimensional structure supported by an acrylic resin film;

[0042] S2. PEO, lithium perchlorate and acetonitrile were weighed in a weight ratio of 20:5:50, uniformly mixed and dissolved, and then 0.4‰ of magnesium chloride was added to the weight ratio of PEO, and the mixture was stirred and mixed to obtain a polymer mixed solution;

[0043] S3. The polymer mixed solution was coated on the sulfide electrolyte membrane and evenly immersed therein to obtain a polymer-sulfide based composite electrolyte membrane with a thickness of 10 μm. The membrane was characterized and analyzed, and the XRD spectrum was shown in Figure 2 The room temperature ionic conductivity is 3.7 mS·cm -1 , AC impedance spectrum is shown in Figure 3 , electrochemical window>5V, linear sweep voltammogram see Figure 4 .

[0044] Example 2

[0045] A method for preparing an ultrathin polymer-sulfide based composite electrolyte membrane comprises the following steps:

[0046] S1. 90 parts by weight of Li3PS4 are dissolved in 270 parts by weight of n-heptane to obtain a mixed solution; 10 parts by weight of pentaerythritol triacrylate and 1% by weight of initiator 184 of pentaerythritol triacrylate are mixed, and then the pre-mixed mixed solution is added, and the mixture is stirred at a speed of 4000 rpm for 20 minutes to obtain a solution containing micro-nano bubbles, and a nano-imprinter is used for UV curing and imprinting, and the imprinting temperature is set to 30°C, the imprinting speed is 50 mm / min, and the imprinting template parameters are as follows: the template shape is cylindrical, the protrusion height is 10 μm, and the spacing is 5 μm. UV curing and imprinting are performed while heating to form a sulfide electrolyte membrane with a three-dimensional structure supported by an acrylic resin film;

[0047] S2. PEO, lithium perchlorate and acetonitrile were weighed in a weight ratio of 50:5:300, uniformly mixed and dissolved, and then magnesium chloride was added in a weight ratio of 0.5‰ of the amount of PEO, and the mixture was stirred and mixed to obtain a polymer mixed solution;

[0048] S3. Apply the polymer mixed solution on the sulfide electrolyte membrane to make it evenly immersed, so as to obtain a polymer-sulfide based composite electrolyte membrane with a thickness of 20 μm.

[0049] Example 3

[0050] A method for preparing an ultrathin polymer-sulfide based composite electrolyte membrane comprises the following steps:

[0051] S1. 98 parts by weight of Li 11 Si2PS 21 Dissolved in 294 parts by weight of n-heptane to obtain a mixed solution; 5 parts by weight of acrylic acid and 5% by weight of initiator 1173 of acrylic acid were mixed, and then the pre-mixed mixed solution was added, and stirred at a speed of 4000 rpm for 20 minutes to obtain a solution containing micro-nano bubbles, and UV-cured imprinting was performed using a nano-imprinter, and the imprinting temperature was set to 70°C, the imprinting speed was 100 mm / min, and the imprinting template parameters were as follows: the template shape was cylindrical, the protrusion height was 80 μm, and the spacing was 10 μm. UV-cured imprinting was performed while heating to form a sulfide electrolyte membrane with an acrylic resin film as a support having a three-dimensional structure;

[0052] S2. PEO, lithium bis(trifluoromethanesulfonate)imide and acetonitrile were weighed in a weight ratio of 30:3:50, uniformly mixed and dissolved, and then 0.6‰ of ferric chloride was added to the weight ratio of PEO, and the mixture was stirred and mixed to obtain a polymer mixed solution;

[0053] S3. Apply the polymer mixed solution on the sulfide electrolyte membrane to make it evenly immersed, so as to obtain a polymer-sulfide based composite electrolyte membrane with a thickness of 100 μm.

[0054] Example 4

[0055] A method for preparing an ultrathin polymer-sulfide based composite electrolyte membrane comprises the following steps:

[0056] S1. 95 parts by weight of Li 3.25 Ge 0.25 P 0.75S4 is dissolved in 285 parts by weight of tetrahydrofuran to obtain a mixed solution; 2 parts by weight of acrylic acid is mixed with TPO whose weight is 1% of the weight of acrylic acid, and then the mixed solution mixed in advance is added, and the mixture is stirred at a speed of 4000 rpm for 20 minutes to obtain a solution containing micro-nano bubbles, and a nano-imprinter is used for UV curing and imprinting, and the imprinting temperature is set to 30°C, the imprinting speed is 50 mm / min, and the imprinting template parameters are as follows: the template shape is cylindrical, the protrusion height is 30 μm, and the spacing is 10 μm. UV curing and imprinting are performed while heating to form a sulfide electrolyte membrane with an acrylic resin film as a support having a three-dimensional structure;

[0057] S2. PEO, lithium hexafluorophosphate and acetonitrile are weighed in a weight ratio of 40:4:200, uniformly mixed and dissolved, and then 0.4‰ of aluminum chloride is added, and the mixture is stirred and mixed to obtain a polymer mixed solution;

[0058] S3. Apply the polymer mixed solution on the sulfide electrolyte membrane to make it evenly immersed, so as to obtain a polymer-sulfide based composite electrolyte membrane with a thickness of 50 μm.

[0059] Example 5

[0060] A method for preparing an ultrathin polymer-sulfide based composite electrolyte membrane comprises the following steps:

[0061] S1. 90 parts by weight of Li3PS4 are dissolved in 270 parts by weight of toluene to obtain a mixed solution; 10 parts by weight of 2-hydroxyethyl acrylate and 3% by weight of initiator 1173 of 2-hydroxyethyl acrylate are mixed, and then the pre-mixed mixed solution is added, and the mixture is stirred at a speed of 4000 rpm for 20 minutes to obtain a solution containing micro-nano bubbles, and a nano-imprinter is used for UV curing and imprinting, and the imprinting temperature is set to 45°C, the imprinting speed is 110 mm / min, and the imprinting template parameters are as follows: the template shape is cylindrical, the protrusion height is 45 μm, and the spacing is 20 μm. UV curing and imprinting are performed while heating to form a sulfide electrolyte membrane with a three-dimensional structure supported by an acrylic resin film;

[0062] S2. PEO, lithium bis(trifluoromethanesulfonate)imide and acetonitrile were weighed in a weight ratio of 35:2:50, uniformly mixed and dissolved, and then magnesium chloride in a weight ratio of 0.4‰ of the amount of PEO was added, and the mixture was stirred and mixed to obtain a polymer mixed solution;

[0063] S3. Apply the polymer mixed solution on the sulfide electrolyte membrane to make it evenly immersed, so as to obtain a polymer-sulfide based composite electrolyte membrane with a thickness of 65 μm.

[0064] Example 6

[0065] A method for preparing an ultrathin polymer-sulfide based composite electrolyte membrane comprises the following steps:

[0066] S1. 45 parts by weight of Li3PS4 and 47 parts by weight of Li7P3S 11 Dissolved in 276 parts by weight of toluene and n-heptane (v:v=1:1) solvent to obtain a mixed solution; 10 parts by weight of 2-hydroxypropyl methacrylate and 2.5% by weight of initiator 184 of methacrylate were mixed, and then the pre-mixed mixed solution was added, and stirred at a speed of 4000 rpm for 20 minutes to obtain a solution containing micro-nano bubbles, and UV-cured imprinting was performed using a nano-imprinter, and the imprinting temperature was set to 30°C, the imprinting speed was 150 mm / min, and the imprinting template parameters were as follows: the template shape was cylindrical, the protrusion height was 5 μm, and the spacing was 5 μm. UV-cured imprinting was performed while heating to form a sulfide electrolyte membrane with an acrylic resin film as a support having a three-dimensional structure;

[0067] S2. PEO, lithium perchlorate and acetonitrile were weighed in a weight ratio of 50:5:300, mixed and dissolved evenly, and then a mixture of magnesium chloride and ferric chloride (m 氯化铁 :m 氯化镁 =1:1), continue stirring and mixing to obtain a polymer mixed solution;

[0068] S3. Apply the polymer mixed solution on the sulfide electrolyte membrane to make it evenly immersed, so as to obtain a polymer-sulfide based composite electrolyte membrane with a thickness of 15 μm.

[0069] Example 7

[0070] A method for preparing an ultrathin polymer-sulfide based composite electrolyte membrane comprises the following steps:

[0071] S1. 90 parts by weight of Li4GeS4 are dissolved in 270 parts by weight of acetonitrile to obtain a mixed solution; 10 parts by weight of a mixture of acrylic acid and 2-hydroxyethyl acrylate (weight ratio of 1:2) and an initiator 1173 whose weight is 5% of the weight of the mixture of acrylic acid and 2-hydroxyethyl acrylate are mixed, and then the mixed solution mixed in advance is added, and the mixture is stirred at a speed of 4000 rpm for 20 minutes to obtain a solution containing micro-nano bubbles, and a nano-imprinter is used for UV curing and imprinting, and the imprinting temperature is set to 60°C, the imprinting speed is set to 50 mm / min, and the imprinting template parameters are as follows: the template shape is cylindrical, the protrusion height is 25 μm, and the spacing is 10 μm. UV curing and imprinting are performed while heating to form a sulfide electrolyte membrane with an acrylic resin film as a support having a three-dimensional structure;

[0072] S2. PEO, lithium perchlorate and acetonitrile were weighed in a weight ratio of 35:5:50, uniformly mixed and dissolved, and then magnesium chloride was added in a weight ratio of 0.1‰ of the amount of PEO, and the mixture was stirred and mixed to obtain a polymer mixed solution;

[0073] S3. Apply the polymer mixed solution on the sulfide electrolyte membrane to make it evenly immersed, so as to obtain a polymer-sulfide based composite electrolyte membrane with a thickness of 40 μm.

[0074] Example 8

[0075] A method for preparing an ultrathin polymer-sulfide based composite electrolyte membrane comprises the following steps:

[0076] S1. 90 parts by weight of Li 10 SnP2S 12 Dissolved in 270 parts by weight of n-hexane to obtain a mixed solution; 2 parts by weight of methyl α-cyanoacrylate and TPO whose weight is 2% of the weight of methyl α-cyanoacrylate are mixed, and then the mixed solution mixed in advance is added, and stirred at a speed of 4000 rpm for 20 minutes to obtain a solution containing micro-nano bubbles, and a nano-imprinter is used for UV curing and imprinting, and the imprinting temperature is set to 30°C, the imprinting speed is 100 mm / min, and the imprinting template parameters are as follows: the template shape is cylindrical, the protrusion height is 39 μm, and the spacing is 20 μm. UV curing and imprinting are performed while heating to form a sulfide electrolyte membrane with an acrylic resin film as a support having a three-dimensional structure;

[0077] S2. PEO, lithium hexafluorophosphate and acetonitrile are weighed in a weight ratio of 20:5:50, uniformly mixed and dissolved, and then zinc chloride in a weight ratio of 0.7‰ of the amount of PEO is added, and stirring and mixing are continued to obtain a polymer mixed solution;

[0078] S3. Apply the polymer mixed solution on the sulfide electrolyte membrane to make it evenly immersed, so as to obtain a polymer-sulfide based composite electrolyte membrane with a thickness of 60 μm.

[0079] The relevant properties of the polymer-sulfide based composite electrolyte membranes prepared in Examples 1 to 8 are shown in Table 1;

[0080] Table 1

[0081]

[0082] Application examples 1 to 8:

[0083] The ultra-thin polymer-sulfide based composite electrolyte membranes prepared in Examples 1 to 8 were respectively 83 (LiNi0.83 Co 0.12 Mn 0.05 O2) and metal lithium negative electrode to assemble into an all-solid-state battery.

[0084] The electrochemical performance of the obtained all-solid-state battery was tested using a Blue Power CT2001A battery test system. The charge and discharge voltage range was 2.8V to 4.2V. The battery was charged and discharged at a rate of 0.1C at room temperature (25 to 30°C). The test results of the capacity retention rate after 400 cycles are shown in Table 2.

[0085] Table 2

[0086]

[0087]

[0088] Among them, the capacity retention rate of the all-solid-state battery prepared in Example 1 after 400 cycles is 88.3%, and the cycle performance curve is shown in FIG. Figure 5 , the rate performance is good. After 0.5C charge and discharge, the capacity is restored better at 0.1C charge and discharge. The rate performance curve is shown in Figure 6 .

[0089] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0090] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing an ultrathin polymer-sulfide based composite electrolyte membrane, characterized in that: The following steps are involved: S1. Mixing an acrylate monomer with a UV initiator, adding a mixed solution of a sulfide electrolyte and a solvent, stirring to obtain a solution containing micro-nano bubbles, and UV curing and imprinting to form a sulfide electrolyte membrane; S2. PEO and lithium salt are added to acetonitrile, mixed evenly, and then chloride is added and stirred to obtain a polymer mixed solution; S3. Apply the polymer mixed solution on the sulfide electrolyte membrane to make it evenly immersed, so as to obtain a polymer-sulfide based composite electrolyte membrane.

2. The method for preparing an ultra-thin polymer-sulfide based composite electrolyte membrane according to claim 1, characterized in that: In S1, the weight ratio of the acrylic ester monomer, the sulfide electrolyte and the solvent is (2-10): (90-98): (270-294).

3. The method for preparing an ultra-thin polymer-sulfide based composite electrolyte membrane according to claim 1, characterized in that: In S1, the acrylate monomer is one or more of acrylic acid, 2-hydroxyethyl acrylate, hydroxypropyl acrylate, methacrylic acid, 2-hydroxyethyl methacrylate, 2-hydroxypropyl methacrylate, methyl α-cyanoacrylate, and pentaerythritol triacrylate.

4. The method for preparing an ultra-thin polymer-sulfide based composite electrolyte membrane according to claim 1, characterized in that: In S1, the UV initiator is one or more of initiator 1173, initiator 184, initiator 907, and TPO; And / or, the amount of UV initiator added is 1-5% by weight of the acrylate monomer.

5. The method for preparing an ultra-thin polymer-sulfide based composite electrolyte membrane according to claim 1, characterized in that: In S1, the solvent is a mixture of one or more of toluene, xylene, chlorobenzene, dimethyl carbonate, n-hexane, acetonitrile, tetrahydrofuran, and n-heptane.

6. The method for preparing an ultra-thin polymer-sulfide based composite electrolyte membrane according to claim 1, characterized in that: In S1, the sulfide electrolyte includes Li3PS4, Li7P3S 11 , Li 11 Si2PS 12 , Li 3.25 Ge 0.25 P 0.75 S4, Li6PS5Cl, Li6PS5Br, Li4GeS4, Li 10 GeP2S 12 , Li 10 SnP2S 12 One or more of .

7. The method for preparing an ultra-thin polymer-sulfide based composite electrolyte membrane according to claim 1, characterized in that: In S2, the weight ratio of PEO, lithium salt and acetonitrile is (20-50):(1-5):(50-300); the amount of chloride added is 0.1-0.8‰ of the weight of PEO.

8. The method for preparing an ultra-thin polymer-sulfide based composite electrolyte membrane according to claim 1, characterized in that: In S2, the lithium salt is one or more of lithium perchlorate, lithium bis(trifluoromethanesulfonate)imide and lithium hexafluorophosphate; And / or, the chloride is one or more of magnesium chloride, aluminum chloride, zinc chloride and ferric chloride.

9. An ultra-thin polymer-sulfide based composite electrolyte membrane, characterized in that: Prepared by any one of the preparation methods of claim 1 to claim 8.

10. Use of the ultra-thin polymer-sulfide based composite electrolyte membrane according to claim 9 in an all-solid-state battery.